Exploring Adaptive Teaching Competencies in Big Data Era - Huda, Miftachul; Maseleno, Andino; Shahrill, Masitah; Jasmi, Kamarul Azmi; Mustari, Ismail; Basiron, Bushrah (International Journal of Emerging Technologies in Learning (iJET), 2017)
In the last decade, the demand of digital tool to support educational process has been emerged among the universities around the world. In big data era, the demand to utilize it in adaptive teaching should be considered to enable the teaching performance especially in accessing the resources. This paper aims to explore the framework model as a way for teachers in adapting big data to help their teaching performance especially in accessing the resources. The literature review was conducted from peer review journals, books and conferences. The findings reveal that process and management skills should be engaged into adaptive teachings competencies. It included commitment in planning, time management, and technology skills. This study is expected to contribute in strengthening teaching performances in the application guideline in the big data era to support assessing the multi-channels of sources of knowledge to extract new insights of value in exploring the adaptive teaching competencies.